The modulation of somatosensory resonance by psychopathic traits and empathy - Marcoux, Louis-Alexandre; Michon, Pierre-Emmanuel; Voisin, Julien; Lemelin, Sophie; Jackson, Philip L. (Frontiers in Human Neuroscience, 2013)
A large number of neuroimaging studies have showed neural overlaps between first hand pain and it’s perception in others. It was also demonstrated that individuals’ factors could modulate the cerebral response to other’s pain. The goal of this study was to investigate the impact of psychopathic traits on the relation between sensorimotor resonance to other’s pain and self-reported empathy. Somatosensory steady-state response (SSSR) to a non-painful stimulation was compared between high (n = 15) and low (n= 15) psychopathic traits participants during a pain observation task. Results showed a significantly greater modulation of SSSR to the observation of pain in others for the high psychopathic traits group. The modulation of SSSR was also positively correlated with affective and relational aspect of psychopathy. Indirect effect of primary psychopathy on the relation between empathic concern and SSSR was confirmed. These results suggest an enhanced sensorimotor resonance in high psychopathic traits men that is dissociated from their affective sensibility toward other’s distress.